Pemasangan Solar Cell Untuk Kapal Nelayan - Ali Basrah Pulungan; Juli Sardi; Hastuti Hastuti; Syaiful Islami; Hamdani Hamdani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Utilization of new renewable energy generation technology can encourage the increase of people's prosperity, especially fishermen. This can be done by utilizing solar energy using solar cell as a source of lighting on the fishing vessel's, thus saving the use of fuel oil. Based on the community service activities aimed at reducing the operational costs of fishermen in the form of Solar cell Installation for fishing boats in the Village Air Tawar Barat District Padang Utara. The implementation method that is given is the installation of solar cell in the ship and training maintenance of solar cell and the introduction of components and hand tools. This activity is held for three days which includes preparation, installation and training and followed by two groups of fishermen, each consisting of 3 members. Each group of fishermen received a complete set of solar cells and installed. This activity has been done well and the solar cell is working properly. Participants hope that such activities can be carried out for the next year, as there are still some fishing boats that are in desperate need. Keywords: Solar Cell, Fishing Ships, Groups of Fishermen